FACTORS ASSOCIATED with EARLY SEX INTERCOURSE amoung YOUNG SCHOOLING CHILDREN in KICUKIRO DISTRICT- RWANDA. - ABELA, Anne M’lurhe; Francis, WABWIRE Paul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Sex and sexuality among adolescents and young people have beenreported to be on increase worldwide. The act is noted to take two directions as eitherby force (rape) or coation. As a result of this, significant number of adolescents (underage populations / < 20 years) is involved in sexual activities at an early age ( earlierthan 20 years). Many young people are exposed to various risks such as unprotectedsex, early pregnancy, STI/STDs, HIV/AIDS and early marriage that follows pregnancy.The aim of this study was to establish the degree of sexuality and identify the factorsassociated with early sexual action / practices among primary school children inKicukiro District, Kigali City.